The Importance of President Zviad Gamsakhurdia’s Political Strategy in the Process of Restoring and De-Occupying Georgia’s Independence: `"I will say the truth, why should I lie." - Tabidze, Manana (Actual Problems of Kartvelology, 2019)
Zviad Gamsakhurdia's strategy includes two stage: the first stage was the political training of the Georgian population to move and gain freedom at the most right moment in the process of disintegration of the Russian Soviet Empire, and the second - much longer, more difficult and dangerous stage of Georgia's spiritual survival and it is related to the performance of it’ s mission. This struggle, if not today, tomorrow, will have an international scale, it will involve people of faith scattered all over the world, guardians of morality and spirituality, knights of the universal battle of evil and good, they will no longer be richer and less rich, armed with nuclear and bacterial weapons. , Many and few ... in this battle good and evil, with stand against each other, the battle for the most important choice - Where do you want to stand. Georgia will be involved in these processes with the ideology of Christianity, Georgian Classical Philosophy and Writing, and ideas of Ilia Chavchavadze and Zviad Gamsakhurdia.